Regímenes internacionales o anarquía internacional - Tomassini, Luciano (Estudios Internacionales, 1987)
Robert O. Keohane, After hegemony : cooperation and discord in the world political economy. Princeton University Press, 1984. John Gerard Ruggie, ed. The antimonies of interdependence : national welfare and international division of labor. Columbia University Press, 1983. Stephen D. Krasner, ed. International regimes. Cornell University Press, 1983